2014
DOI: 10.1016/j.meegid.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

HCV-1b intra-subtype variability: Impact on genetic barrier to protease inhibitors

Abstract: a b s t r a c tDue to error-prone RNA polymerase and the lack of proofreading mechanisms, to the spread worldwide and probable long-term presence in human population, HCV showed a high degree of inter-and intrasubtype genetic variability.Protease inhibitors (PIs), a new class of drugs, have been designed specifically on the HCV genotype 1 NS3 protease three-dimensional structure. The viral genetic barrier limits the efficacy of PIs, and fourteen loci in the HCV NS3 gene are involved in resistance to PIs. A sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Mutations I71 and T72 are compensatory for mutations V55 and M175, and compensatory mutation Q86 is present in the case of mutation at position Q80. 15 In our research, compensatory mutation T72 was observed in 1 patient in relation to substitution at position T54. Also, mutation Q86 was detected in a single patient, who also had a mutation at Q80.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Mutations I71 and T72 are compensatory for mutations V55 and M175, and compensatory mutation Q86 is present in the case of mutation at position Q80. 15 In our research, compensatory mutation T72 was observed in 1 patient in relation to substitution at position T54. Also, mutation Q86 was detected in a single patient, who also had a mutation at Q80.…”
Section: Discussionsupporting
confidence: 47%
“…Ferraro et al detected such mutations in 14% patients infected with HCV genotype 1b at positions V36, F43, T54, I153, R1 55, and D168. 15 In similar studies, Paolucci et al, on the basis of a group of 39 treatment-naïve people infected with HCV genotype 1b, demonstrated the presence of mutations at positions V55, Q80 and M175 in 10% of the patients. 11 In the context of antiviral therapy, mutations decreasing the efficacy of boceprevir and telaprevir are most often detected, which, considering the frequent adverse reactions of these agents, justifies the recommendation to avoid their use in the treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Non-synonymous resistance variants were detected at baseline in the peripheral blood of all patients, supporting the existence of circulating viral populations. The improved detection capacity of the NGS method used here may explain the observation of more highly prevalent and variable mutations at baseline in the peripheral blood than those detected by previous studies in Brazil [11] , [15] , [24] , [25] and other countries [12] , [18] , [26] , [27] . Our results therefore confirm and expand previous research, providing a comprehensive databank of non-synonymous HCV-NS3 variants induced by short-term therapy, which can be of potential importance for future drug resistance association studies involving approved and newly developed PI agents.…”
Section: Discussionmentioning
confidence: 66%
“…The predictive potential of baseline resistance variants remains controversial. Some authors still support routine baseline resistance mutation detection before PI therapy [18] , while others report that resistant variants emerging during PI therapy are the same as those identified at baseline [19] , [20] . However, most studies have investigated emerging resistance mutations late in treatment or post-treatment, i.e., at the time of viral load re-elevation [19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation